THE DEVELOPMENT OF BOARD GAME TO ENHANCE AI AND PROGRAMMING SKILL FOR INDUSTRIAL STUDENTS - Thammabut, Thawach; Osklang, Pracha; Singkeaw, Chan; Wonganu, Piyaporn (Journal of Education and Innovation, 2024)
Programming is an important skill in the artificial intelligence era. Thus, the aim of this research is to design and develop a board game to enhance artificial intelligence and programming skills for industrial students. The study focused on evaluating AI and programming skills, learning achievement, and students’ opinions. The population consisted of 98 first- and second-year high diploma students majoring in electronics at Rajamangala University of Technology Isan, Khon Kaen Campus. The samples were a randomly sampled group of 31 first-year undergraduate students majoring in electronics from the same university. The research used a pre-test and post-test experimental design. The research tools included a board game, a board game quality assessment, an AI and programming skills assessment, a learning performance assessment, and a survey to collect students’ opinions regarding the board game. The results of the research indicated that the board game quality was rated as good ( = 4.20, S.D. = 0.42). The content aspect was at a good level ( = 4.33, S.D. = 0.51). Then, the media aspect was good level ( = 4.25, S.D. = 0.34). Then, the design aspect was at a good level ( = 4.20, S.D. = 0.42). The assessment of AI and programming skills revealed that the students were able to solve problems by decomposition, find patterns, and find the shortest or fastest route. The learning achievement after using the board game showed a significant improvement, with an average post-test score of 19.52 (S.D. = 3.69), indicating a significant difference from the pre-test scores at the 0.05 level of significance. The students’ opinion regarding the board game was highly satisfactory ( = 4.17, S.D. = 0.72). The content aspect was highly satisfactory ( = 4.12, S.D. = 0.71). Then, the media aspect was highly satisfactory ( = 4.19, S.D. = 0.72). Finally, the design aspect was highly satisfactory ( = 4.19, S.D. = 0.71).